Robust and Reprocessable Biorenewable Polyester Nanocomposites In Situ Catalyzed and Reinforced by Dendritic MXene@CNT Heterostructure - Hao Wang; Jiheng Ding; Hongran Zhao; Qinchao Chu; Jin Zhu; Jinggang Wang (Nano-Micro Letters)
Highlights Structurally stable and well-dispersed dendritic MXene@CNT heterostructures with multiple roles (i.e., catalyst, nucleator, and interface enhancer of polyesters) were constructed. Biorenewable MXene@CNT/PBF (MCP) polyester nanocomposites with ultrahigh mechanical strength (≈101 MPa), stiffness (≈3.1 GPa), and toughness (≈130 MJ m−3) were synthesized via MXene@CNT in situ catalytic polymerization. Exceptional reprocessability, gas barrier (e.g., O2 0.0187 barrer), and UV resistance (e.g., resist 85% UVA rays) properties were achieved for the MCP, which can be employed as high-performance and multifunctional packaging materials for plastic replacement.